Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1900/rds.2004.1.80
|View full text |Cite
|
Sign up to set email alerts
|

Polyclonal Anti-T-Cell Therapy for Type 1 Diabetes Mellitus of Recent Onset

Abstract: ■ AbstractThe destruction of pancreatic β-cells in type 1 diabetes mellitus is mediated by autoreactive T-lymphocyte clones. We initiated a prospective randomized controlled trial of polyclonal rabbit anti-T-cell globulin (ATG) in patients with type 1 diabetes within 4 weeks of diagnosis and with residual post-glucagon C-peptide levels still over 0.3 nmol/l. ATG was administered as an initial bolus of 9 mg/kg followed by 3 consecutive doses of 3 mg/kg. An interim analysis was performed to establish whether any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 22 publications
1
52
0
Order By: Relevance
“…Given that Tregs work in a dominant manner through bystander suppression and induce "infectious tolerance" (127), many immunotherapies currently under development target Treg defects identified in preclinical studies, with the goal of restoring Treg function (15,128). Antithymocyte globulin (ATG) has shown promising results in NOD mice and a small clinical trial in patients with T1D (129,130) with tolerogenic potential suggested by its favorable effect on the Treg compartment in mice and humans (130)(131)(132). Recent phase II trials in patients with new-onset T1D showed no clear benefit for ATG monotherapy (133); however, a combination of low-dose ATG and G-CSF tended to preserve β cell function at 12 months following initiation of therapy (134).…”
Section: Stability Of Tregsmentioning
confidence: 99%
“…Given that Tregs work in a dominant manner through bystander suppression and induce "infectious tolerance" (127), many immunotherapies currently under development target Treg defects identified in preclinical studies, with the goal of restoring Treg function (15,128). Antithymocyte globulin (ATG) has shown promising results in NOD mice and a small clinical trial in patients with T1D (129,130) with tolerogenic potential suggested by its favorable effect on the Treg compartment in mice and humans (130)(131)(132). Recent phase II trials in patients with new-onset T1D showed no clear benefit for ATG monotherapy (133); however, a combination of low-dose ATG and G-CSF tended to preserve β cell function at 12 months following initiation of therapy (134).…”
Section: Stability Of Tregsmentioning
confidence: 99%
“…Another study in 2004 reported on 11 patients who received rabbit ATG and were followed for 1 year. Clinical remission was observed in treated patients (two patients reached insulin independency) (Saudek et al 2004). Side effects were transient fever and moderate symptoms of serum sickness (Saudek et al 2004).…”
Section: Polyclonal Antilymphocyte Globulinsmentioning
confidence: 95%
“…Clinical remission was observed in treated patients (two patients reached insulin independency) (Saudek et al 2004). Side effects were transient fever and moderate symptoms of serum sickness (Saudek et al 2004). The START trial (study of thymoglobulin to arrest type 1 diabetes), headed by S. Gitelman at UCSF in partnership with the Immune Tolerance Network is including patients with recent-onset T1D aged 12-35 yr to test the capacity of ATG to halt disease progression.…”
Section: Polyclonal Antilymphocyte Globulinsmentioning
confidence: 99%
“…A pilot trial involving new-onset T1D patients has shown a reduction of insulin requirement (Eisenbarth et al, 1985). In a more recent study, ATG (Fresenius) retarded the loss of C-peptide in new-onset patients without the need for continuous drug administration (Saudek et al, 2004) but additional studies are being performed to confirm these findings.…”
Section: Anti T-lymphocyte Globulin (Atg)mentioning
confidence: 96%